If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2f + -1) = 15 Reorder the terms: 2(-1 + 2f) = 15 (-1 * 2 + 2f * 2) = 15 (-2 + 4f) = 15 Solving -2 + 4f = 15 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4f = 15 + 2 Combine like terms: -2 + 2 = 0 0 + 4f = 15 + 2 4f = 15 + 2 Combine like terms: 15 + 2 = 17 4f = 17 Divide each side by '4'. f = 4.25 Simplifying f = 4.25
| ht=-16t^2+4624 | | -5n-n= | | 3/5(2f-1)=15 | | 8.4/100 | | 4e+8=2 | | .28x+4x=-8.56 | | x^2+20-1360=0 | | .6x+1=19 | | X-13/3 | | 3/4(x-7)^2 | | 20(3r-27)=3(5r+45) | | 3x^2+20x+7=-4x^2+4x+24 | | 6x^2+2x=-7x | | -28.73+(-42.21)=x | | -3.4x+5.1=-22.1 | | (k+4)(k-3)=0 | | 3x*3+x*2=75x+25 | | -28.73+(-42.21)= | | 35/28 | | 3x*3+x*2=75+25 | | 3y+5n+8= | | 15+(-47)=x | | abyse=sb | | -4(y-9)=2y+12 | | (10-3x)*((4x^2)-20x+25)=((x^2)-8x+16)*(2x-5) | | (7x-3)(7x-3)=0 | | -9x+60x=6x | | (-8x^7y)(x^3y^7)=0 | | -9x+60=6x | | (1/7)(1/7)(1/7) | | (2k^3)^4/4k^5 | | 6x-23=14x+49 |